RESULTS OF MONITORING STUDIES ON SHEEP POX IN KAZAKHSTAN IN 2024 - Aliyeva, A.B.; Aidarbekova , D.B.; Almas , E.K.; Serikbayov , O.N.; Barakbayev, K.B.; Kerimbaev , A.A.; Rsaliev , A.S.; Abduraymov , E.O. (Eurasian Journal of Applied Biotechnology, 2025)
This study presents the results of sheep pox monitoring conducted by the Research Institute for Biological Safety Problems (RIBSP) in the Republic of Kazakhstan. To study the epizootic situation of sheep pox, several field expeditions were organized to 15 regions of the country. The primary objectives of the monitoring were to assess the prevalence of the sheep pox virus among small ruminants, identify potential infection foci, and analyze the level of animal immunity. This is due to the paramount importance of controlling the epizootic situation, timely detection of outbreaks, and development of veterinary and sanitary measures for forecasting the spread of sheep pox. The samples were collected from 240 rural districts within 82 rayons (or settlements/farms) across 15 regions of Kazakhstan: Zhambyl, Karaganda, Kyzylorda, Turkestan, Almaty, Zhetysu, Abay, Akmola, West Kazakhstan, Aktobe, North Kazakhstan, East Kazakhstan, Pavlodar, Atyrau, and Mangystau. Sheep blood serum samples were analyzed by enzyme-linked immunosorbent assay (ELISA) for antibodies to the sheep pox virus. The monitoring revealed an uneven distribution of immune animals to the sheep pox virus in Kazakhstan. In the Abay, East Kazakhstan, Aktobe, and Pavlodar regions, no serologically positive animals were detected, indicating the absence of post-vaccination immunity. A low level of immunity was registered in the Akmola, Karaganda, West Kazakhstan, North Kazakhstan, Mangystau, and Atyrau regions. In contrast, the Zhambyl, Turkestan, Almaty, and Zhetysu regions demonstrate the presence of an immune background against sheep pox.